Function-driven design of Bacillus kochii and Filobasidium magnum co-culture to improve quality of flue-cured tobacco - Wu, Xinying; Cai, Wen; Zhu, Pengcheng; Peng, Zheng; Zheng, Tianfei; Li, Dongliang; Li, Jianghua; Zhou, Guanyu; Zhang, Juan; Du, Guocheng (Frontiers in Microbiology, 2023)
Flue-cured tobacco (FCT) is an economical raw material whose quality affects the quality and cost of the derived product. However, the time-consuming and inefficient spontaneous aging is the primary process for improving the FCT quality in the industry. Because FCT is unsuitable for sterilization and is processed in an open environment, bioaugmentation with functional microorganisms is a promising technology. A function-driven co-culture was built in response to the quality-driven need for less irritation and more aroma in FCT. The previous study found that Bacillus kochii SC can degrade starch and protein to reduce tobacco irritation and off-flavors. The screened fungi (Filobasidium magnum F7 with high lipoxygenase activity) could degrade higher fatty acid esters and terpenoids to promote aroma and flavor in the present study. Co-cultivation with strain SC and F7 obtained better quality improvement than mono-culture at an initial inoculation ratio of 1:3 for two days, representing a significant breakthrough in efficiency and a reduction in production costs compared to the more than two years required for the spontaneous aging process. Through the analysis of microbial diversity, predicted flora functions, enzyme activities and volatile compositions within the mono- and co-cultivation, our study showed the formation of a function-driven co-culture between two strains through functional division of labor and nutritional feeding. Herein, the function-driven co-culture via bioaugmentation will become an increasingly implemented approach for the tobacco industry.